A study of risk factors associated with hypertension among the school going children in Puducherry - J., Arun Daniel; R., Kavinilavu (International Journal Of Community Medicine And Public Health, 2018)
Background: High blood pressure in childhood is a predictor of hypertension in adults and its presence is influenced by various clinical and social risk factors. The objectives of the study were to estimate the prevalence of high BP in school going children aged 10 years and above; to assess the risk factors associated with high blood pressure; to compare the prevalence of high blood pressure and associated risk factors among the government and private school going children. Methods: A community-based, cross-sectional study was conducted during July to August 2016 by selecting two schools situated in the urban field practice areas including 423 children aged 10 to 18 years. Data was collected using a structured questionnaire in which dietary habits were assessed using a food frequency questionnaire and anthropometric measurements were made under standard WHO protocol. Results: The overall prevalence of high blood pressure was 12.8%. Factors like age (p=0.005), family history of hypertension (p=0.01), both parents having history of hypertension (p=0.02), poor school performance (p=0.05)and obesity(p=0.001) were significantly associated with high blood pressure among the school children. Conclusions: There were a higher proportion of male hypertensives in the private schools whereas government schools had more female hypertensives.